Dwujęzyczne nazewnictwo geograficzne jako jedno z praw językowych mniejszości narodowych - Abu Gholeh, Magdalena (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
Bilingual topographical indications are a perfect example of linguistic rights of national and ethnic minorities. It is guaranteed by polish legislator in 2005 act. Minorities impact on local communities can be reflected by traditional indications. The aim of this paper is to present polish regulation and both - polish and european - practise on this issue.
Keywords: regional languages; national minorities; minority languages; linguistic rights; bilingual topographical indications; ethnic minorities